1976
DOI: 10.3168/jds.s0022-0302(76)84225-7
|View full text |Cite
|
Sign up to set email alerts
|

A Rumen Linear Programming Model for Evaluation of Concepts of Rumen Microbial Function

Abstract: A linear programming model provides for analysis of general input-output relationships in the rumen, for evaluation of competitive relationships among rumen microbes, and for computation of optimal relationships in the rumen. Eight rumen microbial groups defined on the bases of substrate specificity, nutrient requirements for growth, fermentation products, and relative metabolic activities comprise the central core of the model. Relative metabolic rates of microbial groups calculated from their cell sized were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, the application of these equations to predator-prey (here : protozoa--bacteria) systems has been questioned, because of the biologically unrealistic results (Bazin, 1981) and the structural instability of the model (Brown & Rothery, 1993). Reichl & Baldwin (1976) described a linear programming model of rumen fermentation in which eight microbial groups, including protozoa, were represented. Considerable simplifications of the predicted rumen ecosystem occurred and the authors concluded that additional concepts regarding microbial interactions were required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of these equations to predator-prey (here : protozoa--bacteria) systems has been questioned, because of the biologically unrealistic results (Bazin, 1981) and the structural instability of the model (Brown & Rothery, 1993). Reichl & Baldwin (1976) described a linear programming model of rumen fermentation in which eight microbial groups, including protozoa, were represented. Considerable simplifications of the predicted rumen ecosystem occurred and the authors concluded that additional concepts regarding microbial interactions were required.…”
Section: Discussionmentioning
confidence: 99%
“…The rumen fermentative processes are in the form of linear equations and solved by linear programming techniques, in which the objective function consists of the relative metabolic activities of the eight microbial groups. Considerable simplifications of the rumen microbial groups had to be made though when solving the model, and in their evaluation Reichl and Baldwin (1976) concluded that the concepts represented in the model were not sufficient.…”
Section: Objectives and Brief Description Of Whole Rumen Function Modelsmentioning
confidence: 99%
“…In a large number of solutions of the Reichl and Baldwin model (1975), up to four microbial groups were not represented (i.e. simulated extinction of microbial groups), and the model suggested rumen microflora much simpler than the real rumen microflora (Reichl and Baldwin, 1976). Dijkstra (1994a) only obtained biologically realistic coexistence of populations when autoinhibition effects were included in the model.…”
Section: Microbial Metabolismmentioning
confidence: 99%
“…However, explicit representation of microbial recycling within the rumen in models has received limited attention. Reichl and Baldwin (1976) evaluated effects of engulfment of bacteria by protozoa in their rumen model, and showed significant effects on cell yields and end-products of fermentation in the presence of protozoa. The Cornell model makes an allowance for protozoal predation by decreasing the theoretical maximum growth yield by 20% (Russell et ai, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…(Reichl and Baldwin, 1976). Dijkstra (1994a) (Wallace and McPherson, 1987), inability to utilize ammonia as N source (Coleman, 1986), and selective retention in the rumen (Faichney, 1989), affect key nutritional characteristics.…”
Section: Introductionmentioning
confidence: 99%